Problems in using design an build procurement for educational building / Amirul Afiq Zainal Abidin - Zainal Abidin, Amirul Afiq (Faculty of Architecture, Planning and Surveying, 2013)
This study was carried out to determine and study about procurement and design and build procurement. A 3 project managers from different case studies had been chosen to collect the data. A structured interview was made in order to collect the data. The structured interview consists of 4 sections in order to achieve objectives 1, 2, 3 and 4 as stated in chapter 1. The case studies chosen are renovation project which is GMP project, 13 labs and Uniten project. The other purpose of this study is to identify the common problems in using design and build procurement. On the other hand, the project manager is required to suggest the best practice in using design and build procurement. These parties were also responsible in giving their valuable opinion based on their working experiences at a construction site The overall findings of the study indicate that common problems has been identified based on these three case studies where it is prevalent to design and build procurement that the majority of the case study had experienced. In conclusion, some recommendation has been made in order to avoid problem in using design and build procurement.